Trends in prevalence and acceptance of workplace smoking bans among indoor workers in South Australia. Issue 3 (1996) - Wakefield, M; Roberts, L; Owen, N
Abstract : OBJECTIVE: To compare the reported prevalence and acceptance of bans on smoking in the workplaces of a representative sample of adults in South Australia between 1989 and 1994. DESIGN: Independent cross-sectional representative population surveys. SETTING: South Australian population. PARTICIPANTS: Adults who indicated they were employed mainly indoors, for the years 1989 (875 respondents), 1991 (1472), 1992 (1288) and 1994 (1273). MAIN OUTCOME MEASURES: Percentage reporting total bans on smoking at work; percentage reporting compliance with bans all or nearly all the time; percentage reporting preference for total bans at work. RESULTS: The percentage of indoor workers subject to a total ban on smoking at work increased from 32% in 1989 to 62% in 1994 and preference for a total ban increased during the same period from 26% to 52%. Reported compliance with restrictions and bans was very high. In 1994, 16% of workers still had no restrictions on smoking at work, but only 3% preferred this arrangement. CONCLUSION: The data suggest that smoking bans are now the norm for indoor workers and that further gains in promoting and supporting workplace bans will be made by directing efforts at smaller workplaces, where unrestricted smoking is most prevalent.